1982
DOI: 10.1007/bf00378155
|View full text |Cite
|
Sign up to set email alerts
|

Changes of membrane fluidity in erythrocytes of lead-exposed workers

Abstract: We have studied the effect of lead on the fluidity of erythrocyte membrane to clarify if lead can interact in vivo with biological membranes. Erythrocyte membranes were chosen in our study because a decrease of red cell osmotic fragility is also evident in the absence of laboratory and clinical signs of anaemia. The study was undertaken using the Electron Spin Resonance technique with two spin labels 5-doxyl stearate and 16-doxyl-stearate, which probe the physical state of the polar surface and the inner core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Lead acts directly by inhibiting neutrophil chemotactic activity both in vivo and in vitro (Governa et al 1987(Governa et al , 1988. Furthermore, it can interfere with their cell membrane fluidity in vivo (Valentino et al 1982) and with their cytoplasmic microtubular network in vitro (Bonacker et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Lead acts directly by inhibiting neutrophil chemotactic activity both in vivo and in vitro (Governa et al 1987(Governa et al , 1988. Furthermore, it can interfere with their cell membrane fluidity in vivo (Valentino et al 1982) and with their cytoplasmic microtubular network in vitro (Bonacker et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…In previous experiments in vitro , we have shown that Pb modifies membrane fluidity of erythrocytes of Pb-exposed workers, as well as membrane fluidity of neutrophils. 2,31 Moreover, TNF-a is able to increase the production of IL10. In our Pb-exposed workers, the increased concentration of IL-10 might be secondary to the increased production of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies have focussed on the possible toxic effects of lead on membrane components and have identified a correlation between these effects and lead-induced oxidative damage. 8 *Correspondence: P Varalakshmi, Department of Medical Biochemistry, Dr AL Mudaliar Post Graduate Institute of Basic Medical Sciences, University of Madras (Taramani), Chennai-600 113, India E-mail: drvlakshmi@yahoo.com It is known that lead exerts its influence on the erythrocyte membrane, bringing about changes in the osmotic and mechanical fragility of erythrocytes, 9 enhancement of potassium loss from the cells, 10 reduction of the membrane Na 1 , K 1 -ATPase activity, 11 decreases in the membrane fluidity 12 and changes in the composition of erythrocyte membrane proteins. 13 Lead is also known to inhibit calcium efflux mediated by Ca(Mg)-ATPase.…”
Section: Introductionmentioning
confidence: 99%